(untitled) (Castilla. Estudios de Literatura, 2017)
The present study seeks to interpret the discursive formations inscribed in the novel by Élmer Mendoza, El amante de Janis Joplin (2001), as a transcript of the collective identity around the phenomenon of narcoculture. For this, we will use the Foucault´s reflection on the aspects involved in the process of gestation of discourse as a heuristic axis on which the knowledge of the social imaginary inscribed in the text.